Konstitusi Liturgi Konsili Vatikan II: Prasejarah, Sejarah, dan Naskahnya - Petrus Bine Saramae (Jurnal Orientasi Baru, 2014)
Constitution on the sacred liturgy of the Second Vatican Council speaks about the nature and meaning of liturgy for the life of the Church as well as important directions on the ecclesial renewal through liturgical renewal. This article presents a study, a library research on the history of the respective constitution. This study should help to unfold a rich meaning of this liturgical renewal in the context of an ecclesial renewal in general as well as of a liturgical renewal for the last 50 years after the Council. Significant thoughts of the fathers of the council should serve as source of inspiration, also for our pastoral-liturgical ministry. Finally, the study will indicate some concrete steps to promote a continuation of the liturgical-ecclesial renewal for the life of the pilgrim Church.